The Symbolic Meaning of Attaralu Custom in the Marriage System of the People of Bontolempangan Village, Bukit District, Selayar Islands Regency - Yuliana Yuliana; Muhamad Ramli; Radjab Mansur (Syntax Idea)
The Bontolemngan community, Buki District, Selayar Islands Regency is a traditional village that still maintains their traditional ancestral culture. The marriage system that still exists in the era of globalization is adat attaralu. the purpose of this study is to find out the symbolic meanings contained in the attaralu custom which is carried out in Bontolemngan Village, Buki District, Selayar Islands Regency. This study uses qualitative methods through a case study approach with descriptive analysis including collecting presentation data, displaying data and drawing conclusions. Data collection was carried out using observation, interview, and documentation techniques. The results of this study indicate that there are three main processes in implementing the attaralu custom, namely a'pissalingi, ambaung patingroang, and attaralu, these three processes have deep philosophical meaning for the people of Bontolemapangan Village, Buki District, Selayar Islands Regency.